The Implicature of Humor Utterances inHumor Lucu Ala Gus Dur - Khusnita, Anna Salisah (LANTERN (Journal on English Language, Culture and Literature), 2014)
The utterances produced by the speaker usually contain the certain meaning that is delivered indirectly by the speaker. Thereafter, the writer is interested to investigate the certain meaning that is delivered indirectly by the speaker. In this thesis, the writer uses the humor utterances of Gus Dur in the book Humor Lucu Ala Gus Duras the object of the analysis. In analyzing the data, the writer uses the implicature theory by Grice.Limitation in this research is the use of the implicature that is focused on the cooperative principle by Grice.The purpose of the research is to elaborate the implicit meaning of the utterances in the book Humor Lucu Ala Gus Dur. The other purpose of this research is to show that there are the maxim violations created by speaker and to know the function of using the implicit meaning in the utterances. The implicit meaning can be classified to 4 types based on the illocution; they are representative illocutionary act, expressive illocutionary act, directive illocutionary act, dan commisive illocutionary act. Based on the analysis of the implicature meaning in the utterances, the writer found that the implicit meaning that is delivered by speaker has the functions, that are to give a humor effect, insinuate someone, criticize the government, mockery someone, and warn the reader.